Leadless pacemaker implantation in a patient with congenital azygos continuation of the inferior vena cava - Lanyan Guo; Minxia Zhang; Ying Zhao; Qun Yan; Xuyang Feng; Ling Tao (BMC Cardiovascular Disorders)
Abstract Abstract In case of venous route abnormality during a leadless pacemaker (LP) implantation, it can be challenging if we still performed via the predesigned femoral vein. We report a patient with normal preoperative laboratory and image results, but azygos continuation of the inferior vena cava (IVC) was suspected during the procedure. Then, we decided to change the implantation strategy, the LP implantation was successfully performed via right jugular vein instead of the classical IVC route. Finally, venous computed tomography (CT) angiography was conducted to testify such venous developmental abnormality. Clinical trial number Not applicable